KAJI EKSPERIMEN UMUR LELAH POROS PADA AL 6061-ABU BATUBARA YANG MENDAPAT PERLAKUAN PANAS - Achmad, Zainun; Prasetya, Hendrawan Harry (MEKANIKA: Jurnal Teknik Mesin, 2015)
Fatigue is one of the main causes of failure contruction. Usually material fatigue fracture occurs in poros.Poros a machine element that serves to connect from one machine element to other element . A shaft having adifferent material composition-this different.research has the objective to study the fatigue life of a shaft with amaterial 6061-coal bottom ash results that occur in the home foundry industry after heat treatment t6 and therewere no treatment is done, the results of the specimens to be tested weariness.The method used to determine the fatigue life of a material shaft 6061-ash coal rotary bending fatigue testaccording to standard JIS Z2274 with weights 0.7 Ïƒu and 0.9 Ïƒu of tensile strenght obtained from tensile test.The results of fatigue testing and calculation methods of statistical probability of 10 % , 50 % and 90% of materialsthat are subjected to heat for 2 hours with a load of 0.9 Ïƒu with a probability of 90 % that has the shorte st fatiguelife and fatigue life is highest specimens without heat treatment with a load of 0.7 Ïƒu with a probability of 10 % .This percentage has increased 2x specimen lelah.Jadi age even make the heat treatment cycle of the material to below.Keyword : Fatigue life ,Alumunium,Heat treatment